2022
DOI: 10.1002/advs.202105938
|View full text |Cite
|
Sign up to set email alerts
|

ASCL2 Maintains Stemness Phenotype through ATG9B and Sensitizes Gliomas to Autophagy Inhibitor

Abstract: Autophagy is a highly conserved process that is vital for tumor progression and treatment response. Although autophagy is proposed to maintain the stemness phenotype in adult diffuse glioma, the molecular basis of the link between autophagy and stemness is poorly understood, which makes it impossible to effectively screen for the population that will benefit from autophagy‐targeted treatment. Here, ATG9B as essential for self‐renewal capacity and tumor‐propagation potential is identified. Notably, ASCL2 transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Most reports on its regulation of tumour stemness have appeared in colon cancer and in gliomas. For example, Wang, Li-Hong et al reported that ASCL2 can control the tumour stemness phenotype of glioma cells by regulating the expression of ATG9 protein in glioma cells [ 19 ]. It has also been reported that ASCL2 is highly expressed in mismatch repair-sufficient or microsatellite-stabilised colon cancers and can maintain the stemness of colon cancer tumour cells and activate cancer-associated fibroblasts through the activity of transcription factors, thereby inducing an immune-rejecting microenvironment to inhibit the infiltration of immune cells [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most reports on its regulation of tumour stemness have appeared in colon cancer and in gliomas. For example, Wang, Li-Hong et al reported that ASCL2 can control the tumour stemness phenotype of glioma cells by regulating the expression of ATG9 protein in glioma cells [ 19 ]. It has also been reported that ASCL2 is highly expressed in mismatch repair-sufficient or microsatellite-stabilised colon cancers and can maintain the stemness of colon cancer tumour cells and activate cancer-associated fibroblasts through the activity of transcription factors, thereby inducing an immune-rejecting microenvironment to inhibit the infiltration of immune cells [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence suggests that the capacity for self-renewal and proliferation of CSC can cause metastasis and therapeutic resistance of cancer, leading to recurrence and death in patients [23,24]. More importantly, autophagy is proposed to maintain stemness phenotype in cancer [25]. Notably the therapeutic mechanisms of miR-145-5p were systematically studied, regarding the signaling pathway, effect on LCSC self-renewal activity, and the speci c role in autophagy, for which a variety of techniques including reverse transcription PCR (RT-PCR), western blot, transwell and cell sphere experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the therapeutic efficacy of MRL145 in eradicating LCSCs was also evaluated. The evidence suggests that autophagy is proposed to maintain stemness phenotype in cancer [ 35 ]. Notably the therapeutic mechanisms of miR-145-5p were systematically studied, regarding the signaling pathway, effect on LCSC self-renewal activity, and the specific role in autophagy.…”
Section: Introductionmentioning
confidence: 99%